Damage analysis of human cortical bone under compressive and tensile loadings. Issue 3 (17th February 2022) - Maghami, Ebrahim; Moore, Jason P.; Josephson, Timothy O.; Najafi, Ahmad R.
Abstract: Developing advanced fracture tools can increase the understanding of crack growth trajectories in human cortical bone. The present study investigates fracture micromechanics of human cortical bone under compressive and tensile loadings utilizing a phase field method. We construct two-dimensional finite element models from cortical microstructure of a human tibia cross section. We apply compression on the cortical bone models to create compressive microcracks. Then, we simulate the fracture of these models under tension to discover influential parameters on microcracks formation and post-yielding behavior. The results show that cement lines are susceptible sites to damage nucleation under compression rather than tension. The findings of this study also indicate a higher accumulation of initial damage (induced by compression) can lead to a lower microscopic stiffness as well as a less resistant material to damage initiation under tension. The simulations further indicate that the post-yielding properties (e.g., toughness) can be dependent on different variables such as morphological information of the osteons, the initial accumulation of microcracks, and the total length of cement lines.